The labour share along global value chains: Perspectives and evidence from sectoral interdependence - Federico Riccio; Lorenzo Cresti; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
This article proposes a novel framework to investigate how globalisation affects workers' share of value added. We explore functional income distribution by looking at industrial interdependence and thus identifying GVCs as the unit of analysis; we then track inputs composition and their labour share evolution along the value chains. First, we find widespread heterogeneous patterns across value chains components, accounting for the direct, domestic and foreign requirements of the chains, inside an overall declining trend. Second, we study the evolution of the vertical labour share along development stages. Finally, by means of a shift-share analysis, we investigate what drives such decline in the vertical labour share: albeit country-sector idiosyncratic factors accounted by the within-input component contribute the most, between-input reallocation - GVCs restructuring - matters particularly to detect the role played by foreign contributions. In essence, we provide evidence of a recombination of inputs toward emerging economies and service-based activities. Such recombination negatively impacts upon the overall labour share dynamics. Overall, our methodology contributes to better understanding the process of fragmentation of production and international division of labour by developing a series of novel and fine-grained indicators; in addition, it allows to study the ensuing implication for functional income distribution.
Keywords: F14; J31; O14; 330; Structural Change; Global Value Chains; Labour Share